Multiple functional gastrointestinal disorders linked to gastroesophageal reflux and somatization: A population-based study - Choung, Rok Seon (Neurogastroenterol Motil, 2017)
BACKGROUND: It is unknown why functional gastrointestinal disorders (FGIDs) overlap and limited information exists on risk factors for those with overlap. Our aim was to estimate the prevalence of combinations of FGIDs including reflux (FGIDs-GER), and evaluate potential risk factors for people with multiple disorders in a representative US community. METHODS: A population-based study was conducted by mailing a valid GI symptom questionnaire to an age- and gender- stratified random sample of residents of Olmsted County, MN. Rome III definitions were used to identify people with FGIDs, and GER was defined by weekly or more frequent heartburn or acid regurgitation. The prevalence of people meeting multiple symptom complexes was estimated. Moreover, potential risk factors for people with multiple disorders were evaluated. KEY RESULTS: A total of 3548 people provided data for each of the necessary symptom questions (mean age: 61 years ± 16, 54% female). Among these 3548 subjects, 2009 (57%) had no FGIDs-GER, 906 (26%) had a pure FGID-GER, 372 (10%) had 2 FGIDs-GER, and 261 (7%) had 3 or more FGIDs-GER. Somatization as assessed by a higher somatic symptom checklist score (OR=3.3, 95% CI [2.7,4.1]) was associated with an increased odds for those with 3 or more FGIDs-GER compared to subjects with a pure FGID-GER adjusting for age and gender. CONCLUSIONS & INFERENCES: Symptom complex overlap is common rather than rare in the community. GER is an integral symptom complex associated with both upper and lower FGIDs. Somatization is a strong risk factor for multiple FGIDs.